Exploratory evaluation supported by experimental and modeling approaches of Inula viscosa root extract as a potent corrosion inhibitor for mild steel in a 1 M HCl solution - Adil Mahraz Mohamed; Salim Rajae; Loukili El Hassania; Assouguem Amine; Kara Mohammed; Ullah Riaz; Bari Ahmed; Fidan Hafize; Laftouhi Abdelouahid; Mounadi Idrissi Amine; Hammouti Belkheir; Rais Zakia; et al. (Open Life Sciences, 2024)
The corrosion of metals poses a threat to the economy, the environment, and human health due to undesirable reactions and contaminated products. Corrosion inhibitors, including natural products, can play a key role in protecting metallic materials, especially under challenging conditions. In this study, the roots of the Inula viscosa plant were examined for their ability to act as corrosion inhibitors in a 1 M hydrochloric acid (HCl) solution. Different extracts of the plant were evaluated for their corrosion inhibition capacity in a 1 M HCl solution. The effectiveness of different plant extracts was assessed, including an aqueous extract, an ethanolic extract, and a combined water–ethanol extract. Compounds present in the roots of Inula viscosa were identified using high-performance liquid chromatography. The electrochemical properties of the extracts were studied using various techniques such as open circuit potential, electrochemical impedance spectroscopy, and potentiodynamic polarization. Additionally, surface analysis after immersion was performed using scanning electron microscopy. Electrochemical data revealed that Inula viscosa root (IVR) extracts acted as mixed-type corrosion inhibitors with pronounced cathodic characteristics. The inhibitory efficiency was closely related to the concentration of Inula viscosa (I. viscosa), showing a significant increase with higher concentrations. This resulted in a decrease in corrosion current and an increase in polarization resistance. Notably, inhibitory efficiency reached high levels, up to 97.7% in mixed extract which represents a mixture between water and ethanol. In our study, it was observed that the mixed extract (water + ethanol) allowed for a greater corrosion inhibition compared to the other solvents studied, 97.7%. Surface analyses confirmed the formation of an organic film layer on the steel surface, attributed to the bonding of functional groups and heteroatoms in I. viscosa components. Therefore, this study paves the way for the potential integration of I. viscosa as a promising corrosion inhibition material, offering durable protection against steel corrosion and opening avenues for various related applications.